Pengaruh Customer Review dan Celebrity Endorser terhadap Purchase Intention Dimediasi oleh Trust - Dhea Oktaviani; Ritta Setiyati (JURNAL RISET MANAJEMEN (JURMA), 2025)
Celebrity endorsers play an important role in marketing strategies that can be implemented by Make Over companies by providing accurate and interesting information for their consumers to be able to provide trust, satisfaction so that consumers make continuous purchases of the product. The purpose of this study was to determine the greatest influence on purchase intention. The population of this study is users of Make Over beauty products in Jakarta. This study uses a purposive sampling technique with the criteria of female social media users aged 17-25 years (Generation Z), following the official Make Over social media account, intending to or having purchased Make Over products, and residing in Jakarta which was distributed through a questionnaire to 100 generation z respondents. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. This study shows that the variables of customer review, celebrity endorser, purchase intention and trust can be proven to have a positive influence and the trust variable has the greatest direct influence on purchase intention. Then the trust variable has the greatest indirect influence on customer reviews and purchase intention. This study contributes to Make Over companies in maintaining and increasing purchase intention, which can be seen from several consumer trust factors formed from customer reviews and celebrity endorsers optimally and measurably. For further research, researchers suggest expanding the research area and looking for objects in other fields.